1959
DOI: 10.1126/science.129.3350.718
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlation between Esterase and Protease Activities of Trypsin

Abstract: It is tentatively concluded from ultraviolet and x-ray studies that the two tryptic activities are mediated by overlapping "enzymatic sites." Crucial to this conclusion were studies of the factors which can modify the measured inactivation rates. The data are interpreted in the light of postulated mechanisms of inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1961
1961
1970
1970

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The damaged class of trypsin molecules produced in the photodynamic inactivation experiments differs from the damaged class resulting from the ultraviolet irradiation of tryp~in(~) in that the latter is stable at room temperature for 24 hr, while the former is not. We also observed no difference between the rate of inactivation as measured by the casein assay and the benzoylarginine ethyl ester assay at an illumination temperature of 15"C, while Augenstine (3) found that the rate of inactivation of trypsin by U.V. light at 0°C proceeds at different rates as measured with the hemoglobin, benzoylarginine ethyl ester, and casein assays.…”
Section: Interpretation Of Results With the Hemoglobin And Casein Assaysmentioning
confidence: 52%
“…The damaged class of trypsin molecules produced in the photodynamic inactivation experiments differs from the damaged class resulting from the ultraviolet irradiation of tryp~in(~) in that the latter is stable at room temperature for 24 hr, while the former is not. We also observed no difference between the rate of inactivation as measured by the casein assay and the benzoylarginine ethyl ester assay at an illumination temperature of 15"C, while Augenstine (3) found that the rate of inactivation of trypsin by U.V. light at 0°C proceeds at different rates as measured with the hemoglobin, benzoylarginine ethyl ester, and casein assays.…”
Section: Interpretation Of Results With the Hemoglobin And Casein Assaysmentioning
confidence: 52%
“…Pollard et al (207,208) reported no difference in the rates of inactivat.ion for trypsin measured by both casein assay and by the hydrolysis of the synthet'ic substrate benzoyl arginine ethyl ester. Brustad (62) also found no difference with these two assays, but in accord with model 5 (21) found an apparent increase of 1.7 times in the inactivation rate of trypsin when hemoglobin (in the presence of 5.544 urea) was used for the assay. Fluke reported no difference in the inactivation rate for the activities of xanthine oxidase (106).…”
Section: "After Eflects"mentioning
confidence: 73%
“…24,174,239). The smaller energies imply that weak secondary and tertiary bonds are involved, and the importance of the disruption of cystine groups and hydrogen bonds in UV inactivation has recently been demonstrated (21,26,27). If, as suggested in model 5, ionizing radiation must disrupt a spec& group of bonds, then the energy expended per molecule inactivated, B* (the reciprocal of yield), could be quite different from the energy involved in the crucial excitation process.…”
Section: A Energetic Requirements For Inactivation and Specificationmentioning
confidence: 99%
“…Similarly, the rates of UV-inactivation measured by hemoglobin-urea assay show a temperature independence, in accord with a previous report. 20 Discussion.-Evidence was presented in an earlier discussion of the ultraviolet inactivation of trypsin, indicating that at least three classes or types of trypsin molecules are present in solution after irradiation. 20 The proposed scheme could be represented in the following way, where R1, R2.…”
mentioning
confidence: 96%